Validity of PBL-Based Interactive Multimedia Teaching Material Development Using Powerpoint in Elementary School - Nive tiken; Desyandri; Maria Montessori; Melva Zainil (Postgraduate, University of Mataram, 2024)
Education in the 21st century in the era of the industrial revolution 4.0, information technology is developing rapidly and significantly which causes the influence of technology. By using technology, the learning mindset can shift from teacher-centered to learner-centered. The purpose of this research is to develop interactive multimedia teaching materials based on the PBL model using Powerpoint and Canva in elementary school. This type of research is R&D development research with the ADDIE development model. Data collection and data analysis methods using observation sheets, interview questionnaires and validation instruments as well as qualitative and quantitative descriptive analysis methods. The results of the validation of teaching materials showed a